2014
DOI: 10.1016/j.devcel.2013.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Signaling by p63 Controls Luminal Progenitor Function and Lactation via NRG1

Abstract: Summary The mammary epithelium is organized as a bi-layer of luminal and basal/myoepithelial cells. During pregnancy the luminal compartment expands for milk production, while basal cells are thought to provide structural and contractile support. Here we reveal an unanticipated, pregnancy-specific role of basal epithelia as a central coordinator of lactogenesis. We demonstrate that genetic deletion of the transcription factor p63 (Trp63) gene exclusively within basal cells of the adult gland during pregnancy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 49 publications
9
124
1
1
Order By: Relevance
“…This phenotype was attributed to a block in basal MEC differentiation that was amplified with hormone treatment and pregnancy. Basal MEC specification relies on the expression of P63, and this was recently shown to aid in the regulation of luminal cell growth by promoting the secretion of paracrine factors such a neuregulin (Forster et al 2014). This is a potential point of integration between AR and NOTCH signalling that is discussed in section 'Integration of NOTCH and AR' below.…”
Section: Inducible Expression Of Notch1 In All Mecsmentioning
confidence: 99%
“…This phenotype was attributed to a block in basal MEC differentiation that was amplified with hormone treatment and pregnancy. Basal MEC specification relies on the expression of P63, and this was recently shown to aid in the regulation of luminal cell growth by promoting the secretion of paracrine factors such a neuregulin (Forster et al 2014). This is a potential point of integration between AR and NOTCH signalling that is discussed in section 'Integration of NOTCH and AR' below.…”
Section: Inducible Expression Of Notch1 In All Mecsmentioning
confidence: 99%
“…Stat5a signaling induced by myoepithelial cell-derived neuregulin 1 (Nrg1) is also necessary for MaSC activity (Vafaizadeh et al, 2010;Forster et al, 2014). Nrg1 is expressed in myoepithelial cells in a p63-dependent manner and is detected by luminal cells via the Erbb4 receptor.…”
Section: Luminal Progenitor Cell Differentiationmentioning
confidence: 99%
“…Nrg1 is expressed in myoepithelial cells in a p63-dependent manner and is detected by luminal cells via the Erbb4 receptor. This signaling induces the expression of the Stat5a targets Elf5 and cyclin D1, necessary for luminal and luminal progenitor cell function (Forster et al, 2014). The expansion of progenitor cells also requires Myc, suggesting that this proto-oncogene has a physiological role in mammary development (Moumen et al, 2012).…”
Section: Luminal Progenitor Cell Differentiationmentioning
confidence: 99%
“…In vitro studies have revealed key roles for Notch signaling in mammary stem cells (MaSCs) and luminal cell commitment (26), and the Notch-RBP-J pathway regulates alveoli by maintaining luminal cell fate and preventing uncontrolled basal cell proliferation. TRP63 is a definitive marker of basal cells, and its ablation resulted in impaired alveolar expansion and function during pregnancy (28), which was attributed to a loss of paracrine signaling by Ngr that activated STAT5A in luminal cells via the epidermal growth factor receptor (EGFR). Members of the family of inhibitors of differentiation (ID) also contribute to stem cell activity and differentiation choices between basal and luminal cells.…”
mentioning
confidence: 99%